Evaluasi pelepasan Trichogramma spp. untuk pengendalian penggerek pucuk dan batang tebu - Nurindah Nurindah; Dwi Adi Sunarto; Sujak Sujak (Jurnal Entomologi Indonesia, 2016)
The success and effectiveness evaluation of Trichogramma releases for controlling  sugarcane top borer (Scirpophaga excerptalis (Walker)) and stalk borers (Chilo spp.) have not been intensively evaluated. This research was aimed to evaluate the control technique of sugarcane borer complex by releasing Trichogramma spp. The evaluation approach was performance tests of the parasitoid fitness through determination of reproductive rate and parasitism capacity of the parasitoids. Field observations were also done to obtain the borers’ egg parasitism level in Trichogramma released and unreleased sugarcane fields. The observation was done by collecting the borers’ eggs in such fields and egg parasitism level was recorded. Results showed that releases of Trichogramma chilonis Ishii or Trichogramma japonicum Ashmead were not effectively caused egg parasitism on S. excerptalis or Chilo spp. A hundred % parasitism of S. excerptalis eggs and  77% parasitism of Chilo spp. were caused by Telenomus sp. T. chilonis parasitized only Chilo spp. Reproductive performance of T. japonicum indicated a low reproduction capacity. Mass releases of Trichogramma spp. for controlling the sugarcane borers’ complex in Indonesia has to be reconsidered by taking into account the species and release technique to obtain a successful biocontrol of sugarcane borers’ complex.